Impulsivity Moderates Subjective Responses to Alcohol in Alcohol-Dependent Individuals - Westman, Jonathan G. (Alcohol Alcohol, 2017)
AIMS: Studies of social drinkers indicate that subjective response (SR) to alcohol and impulsivity are risk factors for the development of alcohol use disorder which may be related. It is unclear, however, whether there are significant relationships between SR and impulsivity among individuals with alcohol dependence. Using data from an intravenous (IV) alcohol challenge study, the present study is the first to explore the relationship between impulsivity and SR during alcohol administration among alcohol-dependent individuals. METHODS: Non-treatment-seeking, alcohol-dependent individuals (N = 42) completed the Delay Discounting Task to measure impulsivity and then completed two counterbalanced, placebo-controlled IV alcohol administration sessions, which included assessments of SR at breath alcohol concentration (BrAC) levels of 0.00, 0.02, 0.04 and 0.06 g/dl. RESULTS: Analyses revealed that more impulsive participants experienced higher subjective stimulation and positive mood in response to rising BrACs as compared to less impulsive individuals. More impulsive participants also experienced increased sedation over time regardless of condition (i.e. alcohol vs. saline). CONCLUSION: These findings suggest that among alcohol-dependent individuals, impulsivity is positively associated with the hedonic effects of alcohol as compared to placebo. High impulsivity may characterize a subset of alcohol-dependent individuals who drink to experience the rewarding effects of alcohol.